Muhammad - Mercy to the world / Prof. Dato' Dr. Abu Bakar Abdul Majeed - Abdul Majeed, Abu Bakar (Faculty of Pharmacy, 2023)
The Prophet Muhammad, s.a.w., was born on the 12th day of Rabi al-Awwal, the third month of the Muslim calendar. It signifies spring, the time when seeds split open to generate countless types of plants. Leaves, too, begin to grow in abundance while flowers start blooming. The birth of the Prophet Muhammad also brought unimaginable joy to his close relatives and family friends. He was born an orphan. His father, Abdullah, died months earlier in Medinah while on the way back from a business trip to Syria. His uncle, Abu Lahab, later to become his number one adversary, was so delighted when he heard the good news that he decided to free his slave girl, Thuwaiba, who had brought him the news. According to a saying of the Prophet narrated by Imam Bukhari, because of this good deed, Abu Lahab's punishment in the grave is reduced every Monday, the day the Prophet is born.